Study on structure optimization and applicability of hydrocyclone in natural gas hydrate exploitation - Wei, Na; Qiao, Yi; Liu, Anqi; Zhao, Jinzhou; Zhang, Liehui; Xue, Jin (Frontiers in Earth Science, 2022)
With the development of economy and industry, the consumption of fossil energy is gradually increasing. Currently, natural gas hydrates (NGH) are considered to be an ideal alternative energy due to its large reserve and high energy density. However, the separation of hydrate slurry is a critical step in the exploitation of NGH. In this study, the optimization of the structural parameters based on the conventional three-phase hydrocyclone was carried out using numerical simulation and orthogonal design. At the same time, the separation efficiency criterion E was defined to evaluate the separation efficiency by calculating the sum of the discharge efficiency of water and gas. Analysis of the effect of individual structural factors on the flow field distribution characteristics inside the hydrocyclone using the single factor analysis method. The results showed that: with the combination of structural parameters of s was 2 mm2 × 12 mm2, dz was 28 mm, h was 20 mm, and li was 28 mm, the maximum E of the three-phase hydrocyclone was 1.46. The effect significance of each structural parameter on the separation efficiency from the highest to the lowest was the s, dz, h, and li. In the single-factor analysis, when the s was 2 mm2 × 12 mm2, the tangential velocity, axial velocity, and CH4 volume fraction in the flow field reached the maximum of 13.65 m/s, 4.35 m/s, and 12.4%, respectively. But the minimum water phase volume fraction was 69.9% under this structural parameter condition. When the dz was 36 mm, the maximum decrease value of axial velocity in the flow field was 3.57 m/s, the maximum CH4 volume fraction was 12.4%, and the water volume fraction reached a minimum of 66.3%. The li and the h only had significant effects on the axial velocity and the water volume fraction, respectively. The axial velocity reached a maximum of 4.75 m/s when the li was 32 mm, and the water phase volume fraction reached a maximum of 77.9% when the h was 10 mm. The study of the structural parameters and flow field characteristics of this three-phase hydrocyclone applicable to the solid fluidization exploitation of NGH provides some guidance and suggestions for the separation of hydrate slurry after solid fluidization exploitation of NGH.